Pretreatment loss to follow-up of tuberculosis patients in Chennai, India: a cohort study with implications for health systems strengthening. - Thomas, Beena E.; Subbaraman, Ramnath.; Sellappan, Senthil.; Suresh, Chandra.; Lavanya, J.; Lincy, Savari.; Raja, Agnes Lawrence.; Javeed, B.; Kokila, S.; Arumugam, S.; Swaminathan, Soumya.; Mayer, Kenneth H. (2018)
Background: Pretreatment loss to follow-up (PTLFU) is a barrier to tuberculosis (TB) control in India's Revised National TB Control Programme (RNTCP). PTLFU studies have not been conducted in India's mega-cities, where patient mobility may complicate linkage to care.; Keywords: Tuberculosis, India, Cascade of care, Quality of care, Linkage to care, Initial default, Pretreatment loss to follow-up, Implementation science, Health systems research, Operations research.; Springer Open.